2016
DOI: 10.1177/0163278715616439
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Outcome of an Attempt to Stop Smoking Among Smokers Attending a Smoking Cessation Clinic in Taiwan

Abstract: Studies that have examined gender differences in smoking cessation have produced mixed results. The purpose of the study was to examine whether there are gender differences in long-term smoking abstinence rates in smokers treated with nicotine patches at a smoking cessation clinic in Taiwan, where 39% of men and 5% of women smoke. This study included 1,065 smokers, comprising of 940 men and 125 women. Smokers were invited to attend the clinic every 1-2 weeks for a maximum of eight visits over 90 days, where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…One review demonstrated that women have more difficulty maintaining long-term abstinence than men [ 16 ]. A study on smoking cessation services in Taiwan also showed that women were significantly less likely than men to be abstinent at one year and three years [ 17 ]. The poor long-term outcome in women had been generally attributed to greater concerns about weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…One review demonstrated that women have more difficulty maintaining long-term abstinence than men [ 16 ]. A study on smoking cessation services in Taiwan also showed that women were significantly less likely than men to be abstinent at one year and three years [ 17 ]. The poor long-term outcome in women had been generally attributed to greater concerns about weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…In observational studies, self-reported rates of quitting smoking and the successful smoking cessation rates were similar among older men and women, but higher in women than in men among adults younger than 50 [22]. Among smokers who received NRT in one clinic, women were less likely than men to be abstinent after 1 year [12]. Conversely, our study did not find differential abstinence rates between the sexes, regardless of which smoking cessation medications they had used.…”
Section: Discussionmentioning
confidence: 99%
“…Female smokers have more difficulty in quitting and may respond differently than males to smoking cessation medications [12, 13]. Although some studies observed no differences between males and females in the efficacy of NRT patch, bupropion or varenicline [7, 1315], one recent analysis reported greater efficacy of NRT patch in men [16].…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that females compared to males may be less successful when making a smoking quit attempt (Japuntich et al, 2011;McKee et al, 2015;Smith et al, 2015;Wu et al, 2015). Female smokers may have stronger motivation to reinstate smoking after abstinence than males because they experience more severe negative affect (NA), urge to smoke, and other tobacco withdrawal symptoms during abstinence (Leventhal et al, 2007;Pang and Leventhal, 2013).…”
Section: Introductionmentioning
confidence: 99%